The Effect Of Organizational Commitment, Learning Agility And Digital Pedagogy On The Sustainability Behavior Of The Generation Z Teacher: Penelitian - Hukubun, Yohanis; Wariunsora, Marlen; Sakti, Bayu Purbha; R., Rinovian; Ramli , Akhmad; Anggreni, Made Ayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research focuses on understanding how organizational commitment, learning agility, and digital pedagogy affect the sustainable behavior of Generation Z teachers. This research used the quantitative approach with a survey involving 120 respondents. The findings reveal a positive and significant impact of all variables on the sustainability behavior. Organizational commitment promotes loyalty and professional resilience, learning agility enhances a teacher’s adaptability, while digital pedagogy fosters innovation and a readiness to embrace educational digitalization. This research, theoretically, contributes to the literature on sustainability-based educational management, and, practically, it proposes to educational managers the need to reinforce the supportive research for the Generation Z teachers in order to become resilient, adaptive, and sustainable educators in the digital transformation.